The Influence of Leadership Style and Job Characteristics on Employee Performance of Sritina Primary Inpatient Clinic - Saraswati, Ririn Uke; Soedjatmoko, Soedjatmoko; Moh. Zulkifli, Suripto; Bunga Prawida Suwanto, Fenika (International Journal of Management Science and Information Technology, 2025)
The purpose of this study is to investigate the partial and simultaneous effects of leadership style and job characteristics on employee performance. The high number of employee turnover at Sritina Inpatient Primary Clinic indicates that there is a problem with employee performance. This study collected data through questionnaires and used a quantitative associative analysis approach. The questionnaire was given to 56 respondents with validity, reliability, and normality tests used to process the data.  Data analysis using multiple linear regression analysis, test, partial t test, and simultaneous f test. The results showed that the results of the t test (partial) leadership style had no impact on employee performance, the significance value of 0.381 was greater than 0.05, and the effect of t count 0.884 was less than t table 2.005. Job characteristics have no effect on employee performance with a significance value of 0.449> 0.05 and the effect of t count -0.762 < t table 2.005. However, the findings of the F test simultaneously show that leadership style and job characteristics have a significant and positive effect on employee performance, with a significant value of 0.00 < 0.05, and the impact of F count 10.989 is greater than F table 3.17. This research shows that employees of Sritina Primary Inpatient Clinic can significantly improve their performance by applying effective leadership styles and good job characteristics.